Resource Integration process in Complex Service Systems: Examining Value Co-Creation at Higher Education Institutions - MIR, FARHAN AZMAT; KAUSAR, ABDUL RASHEED; KITCHLEW, NAVEDA (The journal of contemporary issues in business and government, 2021)
This article aims to provide empirical insights on how value co-creation takes place in complex systems; portraying insights from the evolving and complex interaction-based resource integration at HEIs. Tenets of service dominant (S-D) logic (Vargo & Lusch, 2004, 2008) and service science (Maglio & Spohrer, 2008) are used to conceptualize the resource integration process for value co-creation. Multiple Qualitative case studies are used to explore rich experiences of actors during instances of service interactions in higher education institutions (HEIs) and empirical findings are generated from 37 in-depth interviews, observations and web page analysis. The analysis process and findings from the data are systematically displayed using the GIOIA methodology (Gioia, Corley, & Hamilton, 2013). Empirical findings suggested that achievement of sustainable learning outcomes at HEIs requires management of complex interactions that are embedded within diverse yet dependent systems as value is generated through an iterative resource integration process within the overall engagement phase of value co-creation. Furthermore, deliberate replications on key resource integrating practices between human actors and digital systems are discussed to provide clues on interplay of social and technical influences on value co-creation processes. Results could foster expansion of the value co-creation concept and pave way for its operationalization in complex service system settings. Conceptualization of resource integration practices could also guide key stakeholders at HEIs to identify major challenges during value co-creation initiatives. Implications are discussed in the light of roles played by human and digital actors during three critical phases of value co-creation in expedience, engagement and evolution. Acknowledging the fact that opportunities and issues faced by higher education institutions might be like many other industries including tourism, public service, nursing and others; yet aim of using the case studies for in depth insights in this paper limits the statistical generalizability.